Contamos anécdotas - Godos Lopez, Ignacio (2018)
Throught the development of this learning sessión is intended to bueld in the student the necessary information to express and produce messages. It will be taken into account the way in which students express them selves and understand messages will be taken into account, if they’re able to communicate by making clear to others what they want to express and understand what others want to communicate._x000D_ The habit of Reading and writing for pleasure will be stimulated, that they write their anecdotes, stories, etcétera, that they socialize with their readings, so that they’ll have the opportunity to assess what’s learned through Reading, organizing what they learned and awakening curiosity the others by read the text. The motivating Reading is the “kite stuck” waiting to be achieved the established objectives.